Handbook of polycarbonate science and technology - LeGrand, Donald G.; Bendler, John T. (Plastics engineering, 2000)
Summarizes research and progress in understanding the fundamental molecular properties of polycarbonates by covering history, theory, modeling, and spectroscopy. Offers the first comprehensive survey of polycarbonates in over 30 years.